2013
DOI: 10.1371/journal.ppat.1003422
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-9 and IL-21 Mediate Cross-regulation between Th17 and Treg Cells during Acute Hepatitis C

Abstract: Loss of CD4 T cell help correlates with virus persistence during acute hepatitis C virus (HCV) infection, but the underlying mechanism(s) remain unknown. We developed a combined proliferation/intracellular cytokine staining assay to monitor expansion of HCV-specific CD4 T cells and helper cytokines expression patterns during acute infections with different outcomes. We demonstrate that acute resolving HCV is characterized by strong Th1/Th17 responses with specific expansion of IL-21-producing CD4 T cells and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(141 citation statements)
references
References 80 publications
4
134
1
2
Order By: Relevance
“…Furthermore, in vitro studies have found that Gal-9 induces differentiation of naive T cells to Treg cells, and suppresses differentiation to Th17 cells. 47,48,75 Given the multiple functions of Gal-9 in regulating CD4 + T cell responses, 48 this may be in part driven by Gal-9. 48,[76][77][78] Overall, our results demonstrate that Gal-9 levels are an early biomarker of HIV infection and likely track HIV viremia through primary infection and then persist into chronic infection even in subjects exhibiting good viral control.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in vitro studies have found that Gal-9 induces differentiation of naive T cells to Treg cells, and suppresses differentiation to Th17 cells. 47,48,75 Given the multiple functions of Gal-9 in regulating CD4 + T cell responses, 48 this may be in part driven by Gal-9. 48,[76][77][78] Overall, our results demonstrate that Gal-9 levels are an early biomarker of HIV infection and likely track HIV viremia through primary infection and then persist into chronic infection even in subjects exhibiting good viral control.…”
Section: Discussionmentioning
confidence: 99%
“…HCV acutely infected subjects were recruited among high-risk HCV-seronegative injection drug users participating in the Montreal Hepatitis C Cohort at the Saint-Luc Hospital of the University of Montreal Health Center as previously described (44). Blood samples were processed and analyzed as previously described (45). The institutional ethics committee at the University of Montreal Hospital Research Center approved the human study (SL05.014).…”
Section: Methodsmentioning
confidence: 99%
“…CD26? Th17 cells capable of producing IL-21 was reported in patients who spontaneously cleared HCV [94]; the functional relevance if this result needs to be further explored.…”
Section: T Cell Responses In Chronic Hcv Infectionmentioning
confidence: 99%